Integration of School Rules by Classroom Teachers in Forming Student Discipline in Elementary Schools - Annisaa Lady Angela; Achmad Fathoni (International Journal of Elementary Education, 2022)
School rules are very important which must be obeyed and carried out by every member of the school according to existing regulations, to prohibit students from getting used to discipline. Therefore the purpose of this research is to analyses how to guide students by the principal and teachers regarding information about school rules. In this study the method used is descriptive qualitative. Data collection techniques used in this research are observation of students, interviews, and documentation. The resource persons in this study were school principals and teachers of grades 1-6. The data analysis used was interactive by Miles & Huberman namely data collection, data reduction, data presentation, and drawing conclusions. From the analysis of the research data, the following research results were obtained. First, the school's efforts in fostering the character of student discipline through the School Rules where schools must know the personality of students, develop student character together with the principal and teachers and support good facilities and infrastructure. Second, the impact of involving students' disciplinary character through the School Rules means that students become role models in behavior, are responsible for what they do and also become achievements.